Mobile health application (WeFit) among community-dwelling older adults: Development, validation, acceptance, and usability study - Nurul Asilah Ahmad; Arimi Fitri Mat Ludin; Divya Vanoh; Noorlaili Mohd Tohit; Zahara Abdul Manaf; Shahrul Azman Mohd Noah; Suzana Shahar (Digital Health)
Background Technology advancement along with the increase in the older adults’ population leads to the creation of health applications. The combination of exercise, nutrition, and cognition should be studied carefully in improving older adults’ health. Objective The purpose of this study is to develop a health application, WeFit contains these three components and to determine its content validity, acceptability, and usability. Methodology This study is a design and development study involving three phases. The first phase is the need analysis involving a review on 16 mobile applications available in Google play and iTunes App store as well as a review of six articles for identifying the perception of older adults in using mobile applications. Second phase is mobile application development and content validity. The content validity was determined using the Content Validity Index for Individual Items (I-CVI). Phase 3 evaluated the acceptance of the WeFit mobile application among older adults and health practitioners. Results Phase 1 indicated that half of the applications reviewed (50.0%) had physical activity component and the other half (50.0%) had a cognitive component, and none on nutrition. No application is reported to have all three components. In Phase 2, WeFit health application containing the three components was developed where users can view exercise and food recommendations and play cognitive games. WeFit had an I-CVI value of 0.98. With respect to acceptability, majority of the study participants (93.3%) understood the WeFit's content and the graphics used were appropriate. The usability study found that the majority of the older adults were satisfied with the interface and content. All health practitioners (100%) agreed WeFit is easy to use and agreed that it can guide them in giving medical advices. Conclusion WeFit mobile app has been successfully developed, validated, and tested for acceptance among the older adults and health practitioners.